2007
DOI: 10.5194/acp-7-6161-2007
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of atmospheric mineral dust due to electric field

Abstract: Abstract. Optical polarimetry observations on La Palma, Canary Islands, during a Saharan dust episode show dichroic extinction indicating the presence of vertically aligned particles in the atmosphere. Modelling of the extinction together with particle orientation indicates that the alignment could have been due to an electric field of the order of 2 kV/m. Two alternative mechanisms for the origin of the field are examined: the effect of reduced atmospheric conductivity and charging of the dust layer, the latt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 74 publications
2
69
2
Order By: Relevance
“…Li et al, 2010 and references therein). The presence of an electric field in dust aerosol layers was indeed proposed by Ulanowski et al (2007) to explain the alignment of non-spherical particles and polarisation effects in a dust plume over the Canary Islands. Nicoll et al (2011) also report charged particles within Saharan dust layers with two balloon soundings performed above the Cape Verde islands.…”
Section: Indirect Detection Of Possible Charged Particlesmentioning
confidence: 99%
“…Li et al, 2010 and references therein). The presence of an electric field in dust aerosol layers was indeed proposed by Ulanowski et al (2007) to explain the alignment of non-spherical particles and polarisation effects in a dust plume over the Canary Islands. Nicoll et al (2011) also report charged particles within Saharan dust layers with two balloon soundings performed above the Cape Verde islands.…”
Section: Indirect Detection Of Possible Charged Particlesmentioning
confidence: 99%
“…Colarco et al (2003) and Yang et al (2013) discuss the impact of different shapes of dust particles on falling speed and gravitational settling behavior. Ulanowski et al (2007) observed that dust layers have an impact on the atmospheric electric field and argue that dust particles can become charged (when colliding with themselves or the underlying surface) and may be vertically aligned in the electric field, and conclude that these charging effects influence the downward transport of dust. Radiosonde wind profiles always show variations in wind direction and wind velocity throughout the SAL vertical column and thus indicate the potential for some wind-shear-induced turbulent mixing (including upward motion of dust particles).…”
Section: Conceptual Model Versus Lidar Observations (Part 2)mentioning
confidence: 99%
“…Yang et al (2013) discusses the possibility that different shapes of small (less irregularly shaped) and large particles (more irregularly shaped) may have an impact on falling speed and thus the vertical dust distribution. Ulanowski et al (2007) observed that dust layers have an impact on the atmospheric electric field, and argue that dust particles can become charged (when colliding with themselves or the underlying surface) and may be vertically aligned in the electric field, and conclude that these charging effects influence the downward transport of dust.…”
Section: Dust Mass Profiles: Macc/cams Nmmb/bsc-dust and Skiron Simmentioning
confidence: 99%
“…The R/V Meteor lidar observations, the SALTRACE observations at Barbados, as well as spaceborne lidar measurements (CALIOP: Cloud-Aerosol Lidar with Orthogonal Polarization) over the tropical Atlantic suggest that other processes besides gravitational settling of dust must be active in the SAL and weaken the dust removal strength caused by the fallout of dust particles (Ulanowski et al, 2007;Nicoll et al, 2011;Yang et al, 2013;Colarco et al, 2003;Gasteiger et al, 2017;Haarig et al, 2017a). During SALTRACE, the lidars generally observed an almost height-independent vertical profile of the dust-related particle depolarization ratio within the SAL which indicates well-mixed conditions rather than an accumulation of larger particles in the base region of the SAL as would be the case as a result of gravitational settling.…”
Section: Dust Mass Profiles: Macc/cams Nmmb/bsc-dust and Skiron Simmentioning
confidence: 99%